2022
DOI: 10.3389/fmolb.2022.838006
|View full text |Cite
|
Sign up to set email alerts
|

ROS-Induced DCTPP1 Upregulation Contributes to Cisplatin Resistance in Ovarian Cancer

Abstract: Cisplatin resistance hinders the improvement of the prognosis of patients with ovarian cancer. Cisplatin induces cancer cell apoptosis by inducing reactive oxygen species (ROS). dCTP pyrophosphatase 1 (DCTPP1) is a newly discovered dNTP pyrophosphatase. This study aimed to identify the role of DCTPP1 in oxidative stress and cisplatin response of ovarian cancer. Our results indicates cisplatin-induced ROS generation was responsible for the upregulation of DCTPP1 in ovarian cancer cells, whereas DCTPP1 knockdown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…The GEPIA2 online analysis tool found that the DCTPP1 mRNA expression level in OC tissue was significantly higher than that in normal ovarian tissue (p < 0.05) (Figure 1A), which is consistent with our previous work. 15 As shown in Figure 1B,C, time-dependent ROC curves by Sangerbox online analysis tool show that higher expression levels of DCTPP1 mRNA were significantly correlated with shorter OS (log-rank p = 0.028) and DFS (log-rank p = 0.02). We use the standard metric of Area Under the Curve (AUC) of an ROC curve as the comparison metric, the best AUC of the ROC curve for OS and DFS was 0.55 (95% CI, 0.48-0.63) and 0.56 (95% CI, 0.48-0.63).…”
Section: Dctpp1 May Be a Potential Tumour Promoter In Ocmentioning
confidence: 79%
See 2 more Smart Citations
“…The GEPIA2 online analysis tool found that the DCTPP1 mRNA expression level in OC tissue was significantly higher than that in normal ovarian tissue (p < 0.05) (Figure 1A), which is consistent with our previous work. 15 As shown in Figure 1B,C, time-dependent ROC curves by Sangerbox online analysis tool show that higher expression levels of DCTPP1 mRNA were significantly correlated with shorter OS (log-rank p = 0.028) and DFS (log-rank p = 0.02). We use the standard metric of Area Under the Curve (AUC) of an ROC curve as the comparison metric, the best AUC of the ROC curve for OS and DFS was 0.55 (95% CI, 0.48-0.63) and 0.56 (95% CI, 0.48-0.63).…”
Section: Dctpp1 May Be a Potential Tumour Promoter In Ocmentioning
confidence: 79%
“…ROS in OC cells, increasing their sensitivity to cisplatin treatment. 15 Therefore, in this study, we examined the accumulation of ROS in SKOV3/S cells and SKOV3/DDP cells after cisplatin treatment.…”
Section: Skov3/ddp Counteract the Cytotoxic Effects Of Cisplatin By A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, HMGB3 is also a prototypical marker of breast cancer progression but worsens cancer progression primarily by promoting formation of breast layers of breast cancer cells [ 40 , 41 ]. DCTPP1 is an oncogene regulated by the oncogenic factor miR-378a-3p, and this gene facilitates breast cancer cell proliferation through the interference of DNA repair signaling pathway [ 42 , 43 ]. The phenomenon of overexpression of SHCBP1 in breast cancer has been studied, and cellular experiments have demonstrated that this gene directly regulates breast cancer cell proliferation and promotes the cell cycle [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in intracellular ROS levels in OC has been shown to contribute to therapeutic resistance. For instance, an increase in ROS in OC results in the overexpression of dCTP pyrophosphatase I (DCTPP1), which has a role in DNA damage repair and plays a major contribution to cisplatin resistance [ 181 ]. By a differing mechanism, the upregulation of calcium/calmodulin-dependent protein kinase II gamma (CAMK2G) in response to increasing levels of ROS reprograms the cellular redox system through the phosphorylation of inositol triphosphate3-kinase B (ITPKB), resulting in adaptive redox homeostasis and increased resistance to cisplatin treatment [ 182 ].…”
Section: Potential Mechanism Of Ros In Therapeutic Resistance In Ovar...mentioning
confidence: 99%